The Impact of Programmed Learning Strategies and Integrative Information Fragmenting in the Development of Psychological Compatibility and Capabilities and Distinctive Explosive Speed and Completion of the Effectiveness of the Long Jump for Students - Zuhair Saleh Majhool (Journal of Global Pharma Technology, 2016)
There is a weakness in the psychological compatibility and physical abilities (the explosive ability and speed advantage) in some students and to contribute to improving the achievement in the long jump activity and in view of that most of the events, including the effectiveness of long jump depends mostly on the strength and speed in improving achievement, which called for researchers to study this phenomenon a scientific study, being a phenomenon that occurs for some students and lead to the decline of their levels and achievements, despite the continued training. The goal of the research to:To recognize the impact of programmed and integrative learning strategies of fragmented information in the development of psychological compatibility and explosive capabilities and distinctive speed and achieve the effectiveness of long jump for students.Identify which strategies have the advantage in developing psychological compatibility and explosive capabilities and distinctive speed and achieve the long jump activity of students.The researchers used the experimental approach in the design of the two equal groups. The research community is determined by the first stage students at the Faculty of Physical Education and Sports Sciences at the University of Babylon for the 2017-2018 academic year. The number of students is 92 students. The sample was randomly selected by 40 students. (The first with the integrated strategy for fragmented information, the second with the programmed learning strategy), the conclusions were:The first group (integrated strategy of fragmented information) developed psychological compatibility and explosive capabilities and distinctive speed and achieve the effectiveness of the long jump for students.The second group (programmed learning strategy) developed psychological compatibility and explosive capabilities and distinctive speed and the completion of long jump activity of students.There is a preference for the first group (integrated strategy of fragmented information) in the development of psychological compatibility and explosive capabilities and distinctive speed and to achieve the effectiveness of the long jump for students.Keywords: Integration of fragmented information programmed learning, Psychological compatibility and long jump activity.